2021
DOI: 10.1097/anc.0000000000000830
|View full text |Cite
|
Sign up to set email alerts
|

Parental Participation in NICU-Based Occupational Therapy, Physiotherapy, and Speech and Language Therapy

Abstract: BackgroundParent involvement in neonatal care is beneficial to families and infant outcomes. Few studies have explored parental experiences of neonatal therapy participation. PurposeThis study had two purposes: 1) to explore parental attitudes and beliefs about participating in neonatal therapies, and 2) to identify barriers and facilitators to parental involvement and suggest ways to optimise neonatal therapy services. MethodsThe study design and data analysis were informed by constructivist grounded theory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The practical knowledge parents learned through therapeutic interventions contributed to reflections of their role as a parent ( Benzies and Magill-Evans, 2015 ), and helped parents be more comfortable in parenting their infant ( Lee et al, 2019 ; Edney and Mchugh, 2021 ; Van Den Hoogen et al, 2021 ). The analysis revealed that administering the intervention gave a liberating feeling of empowerment and an affirmation to their role as a parent ( Kynø et al, 2013 ; Benzies and Magill-Evans, 2015 ; Håkstad et al, 2016 ; Lee et al, 2019 ; Øberg et al, 2019 ; Edney and Mchugh, 2021 ; Van Den Hoogen et al, 2021 ; Ochandorena-Acha et al, 2022 ). Parents felt empowered through being the one in charge, being responsible for the caring for their infant and being the one promoting infant development ( Kynø et al, 2012 ; Håkstad et al, 2016 ; Øberg et al, 2019 ; Baraldi et al, 2020 ; Ochandorena-Acha et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The practical knowledge parents learned through therapeutic interventions contributed to reflections of their role as a parent ( Benzies and Magill-Evans, 2015 ), and helped parents be more comfortable in parenting their infant ( Lee et al, 2019 ; Edney and Mchugh, 2021 ; Van Den Hoogen et al, 2021 ). The analysis revealed that administering the intervention gave a liberating feeling of empowerment and an affirmation to their role as a parent ( Kynø et al, 2013 ; Benzies and Magill-Evans, 2015 ; Håkstad et al, 2016 ; Lee et al, 2019 ; Øberg et al, 2019 ; Edney and Mchugh, 2021 ; Van Den Hoogen et al, 2021 ; Ochandorena-Acha et al, 2022 ). Parents felt empowered through being the one in charge, being responsible for the caring for their infant and being the one promoting infant development ( Kynø et al, 2012 ; Håkstad et al, 2016 ; Øberg et al, 2019 ; Baraldi et al, 2020 ; Ochandorena-Acha et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Later, taking an active part in the intervention contributed to the feeling of being more capable of handling and playing with their infant ( Lee et al, 2019 ; Ochandorena-Acha et al, 2022 ). Involvement in the intervention was perceived as regaining control over their child’s destiny and helping their child develop ( Edney and Mchugh, 2021 ). Being the provider made them feel complete as a parent ( Lee et al, 2019 ; Øberg et al, 2019 ; Van Den Hoogen et al, 2021 ) and gave a touch of normalcy to the family ( Håkstad et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultimately, therapists did not see infants at a higher frequency than standard of care practice, but they enjoyed providing more intensive therapeutic care with parents through the TEMPO intervention. In alignment with best practice in clinical care [ 12 , 13 , 14 , 35 ], TEMPO provided the structure to ensure that parents were delivering recommended interventions at each stage of the infant’s development. Therapists felt that they were optimizing what they could offer the infant through regular interactions with parents.…”
Section: Discussionmentioning
confidence: 99%